Japanese Encephalitis (JE): Population at Risk and Strategies to Control in India - Sourabh Saxena; Priti Chaudhary; Ashish Chauhan (Medsci Publications, 2018)
Currently, an estimated 3 billion people live in the 24 countries, mainly in the WHO South-East Asia and Western Pacific Regions, considered at risk of JE. The case-fatality rate can be as high as 30%, with 20-30% of survivors suffering permanent intellectual, behavioral, or neurological problems. Overall annual incidence in endemic countries has been estimated at 5.4/100000 in the 0-14 year age group, and 0.6/100000 in those aged more than 15years.In lack of convincing data on actual disease burden due to inappropriate diagnostic facilities and strong quality surveillance mechanism for the virus in India, some researchers has shown there concern to continue a national program to control a highly localized illness with around 1000 cases and 200 odd deaths every year. Immunization as well as other strategies like periodic fogging, promotion of personnel protective measure (protective clothing, use of mats/coils/repellant/aerosol and establishment of paediat- ric Intensive care unit in endemic districts has been advocated since long. Presently out of total 231 JE endemic districts across 22 states, campaign activity has been completed in 230 districts and JE vac- cination has been started as a part of routine immunization. In last few years cases of adult Japanese encephalitis has been reported from identified JE endemic districts.Accordingly, 31 endemic dis- tricts were identified across 3 states where adult JE vaccination campaigns were recommended. The adult JE campaign, covering adults aged 15-65 years, have been completed in these 31 districts wherein 33 million adults were vaccinated against JE.